(untitled) (Scientific journal of the Fergana State University, 2026)
The results of our algological research conducted in the water bodies of several fishery farms in the Fergana Valley — Namanganbaliq, Damko‘l, and Yormozor — showed that during the period from 2009 to 2022, a total of 163 species and varieties of algae were identified, 42 of which were indicator-saprobic algae. These indicator-saprobic algae belong to 3 divisions, 7 classes, 9 orders, 14 families, and 24 genera, comprising 42 species and varieties in total.